PERAN PROMOSI DALAM MEMODERASI PENGARUH BIAYA, LAMA USAHA DAN TENAGA KERJA TERHADAP PENDAPATAN PELAKU UMKM DI KOTA DENPASAR - Setia Wirawan, I Komang Gede; Karmini, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.10.TAHUN.2023, 2023)
The Micro, Small and Medium Enterprises (MSME) sector is one of the economic sectors that has a role in national economic development. The existence of the MSME sector will strengthen the foundation of the regional economy and become a means of promoting regional economic wealth. This study aims to analyze the effect of length of business, cost, labor and promotion on the income of MSME actors and the role of promotion in moderating the effect of length of business, costs and labor on the income of MSME actors in Denpasar City. Samples were taken as many as 100 MSME actors in Denpasar City with the stratified proportional sampling method. The data analysis technique used is Moderated Regression Analysis (MRA). The results of the analysis show that costs, length of business, labor, and promotions have a positive effect on the income of MSMEs in Denpasar City. Promotion moderates the effect of cost, length of business and labor on MSME income in Denpasar City.